11th Symposium on Haptic Interfaces for Virtual Environment and Teleoperator Systems, 2003. HAPTICS 2003. Proceedings.
DOI: 10.1109/haptic.2003.1191291
|View full text |Cite
|
Sign up to set email alerts
|

Haptic aided design: a case study

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…A good review of haptic algorithm can be found in Ref. [4,5], where the terminology and fundamentals of haptic simulation are also detailed. One primary difficulty of realistic haptic modeling and rendering is speed requirement.…”
Section: Introductionmentioning
confidence: 99%
“…A good review of haptic algorithm can be found in Ref. [4,5], where the terminology and fundamentals of haptic simulation are also detailed. One primary difficulty of realistic haptic modeling and rendering is speed requirement.…”
Section: Introductionmentioning
confidence: 99%